Comparative efficacy of topical minoxidil alone against combination of topical minoxidil and platelet rich plasma in women with female pattern hair loss-A pilot, open randomised trial - Akanksha Agarwal; Vibhu Mendiratta (Wolters Kluwer Medknow Publications, 2023)
Background: Female pattern hair loss (FPHL) affects a significant proportion of population and poses a major therapeutic challenge. Aims and Objectives: To compare the efficacy and safety profile of combination of topical minoxidil 2% plus platelet rich plasma (PRP) (group 1) and topical minoxidil 2% solution alone (group 2) in women having FPHL. Materials and Methods: 26 females with FPHL were randomised into two treatment groups. They were evaluated for increase in hair density, reduction in hair pull test (HPT), patient satisfaction score (PSS) and side effects. Results: Mean change of 34.92 ± 8.39 hairs/cm2 in group 1 (P < 0.001) and 31.21 ± 8.30 hair/cm2 in group 2 (P < 0.001) was seen. 16.7% and 28.6% patients in Group 1 and 2, respectively, had PSS of highly satisfied. The reduction in HPT was significant with P = 0.0123 (group 1) and P = 0.0128 (group 2). There was no statistically significant difference between the two groups. No major side effects were reported. Conclusion: Minoxidil-PRP combination therapy is an effective modality for FPHL but is not superior to topical 2% minoxidil therapy alone. PRP is a promising option in patients with minoxidil related compliance issues.